Odpowiedź :
Zad.1.
m1 = 10kg
m2 = 2kg
v1 = 1m/s
v2 = 7m/s
v3 = ?
Po = Pk
m2*v2 – m1*v1 = (m1+m2)*v3
v3= (m2*v2 – m1*v1) / (m1+m2)
v3 = (2kg*7m/s – 10kg*1m/s) / (10kg+2kg)
v3 = 0,33 m/s
Wózek z kulą porusza się w tym kierunku, w którym toczyła się kula.
Zad.2.
m1= 11000 kg
m2= 54 kg
v1 = ?
v2 = 900 m/s
Po = Pk
Po=(m1+m2)* V
V= 0 – na początku działo jest w spoczynku
0=m2*v2 – m1*v1
m1*v1 = m2*v2
v1= (m2*v2) / m1
v1= (54kg*900m/s) / 11000kg
v1 = 4,42 m/s
m1 = 10kg
m2 = 2kg
v1 = 1m/s
v2 = 7m/s
v3 = ?
Po = Pk
m2*v2 – m1*v1 = (m1+m2)*v3
v3= (m2*v2 – m1*v1) / (m1+m2)
v3 = (2kg*7m/s – 10kg*1m/s) / (10kg+2kg)
v3 = 0,33 m/s
Wózek z kulą porusza się w tym kierunku, w którym toczyła się kula.
Zad.2.
m1= 11000 kg
m2= 54 kg
v1 = ?
v2 = 900 m/s
Po = Pk
Po=(m1+m2)* V
V= 0 – na początku działo jest w spoczynku
0=m2*v2 – m1*v1
m1*v1 = m2*v2
v1= (m2*v2) / m1
v1= (54kg*900m/s) / 11000kg
v1 = 4,42 m/s
zad 1
m1 = 10kg
m2 = 2kg
v1 = 1m/s
v2 = 7m/s
v3 = ?
Po = Pk
m2*v2 – m1*v1 = (m1+m2)*v3
v3= (m2*v2 – m1*v1) / (m1+m2)
v3 = (2kg*7m/s – 10kg*1m/s) / (10kg+2kg)
v3 = 0,33 m/s
Wózek z kulą porusza się w tym kierunku, w którym toczyła się kula.
zad 2
m1= 11000 kg
m2= 54 kg
v1 = ?
v2 = 900 m/s
Po = Pk
Po=(m1+m2)* V
V= 0 – na początku działo jest w spoczynku
0=m2*v2 – m1*v1
m1*v1 = m2*v2
v1= (m2*v2) / m1
v1= (54kg*900m/s) / 11000kg
v1 = 4,42 m/s
m1 = 10kg
m2 = 2kg
v1 = 1m/s
v2 = 7m/s
v3 = ?
Po = Pk
m2*v2 – m1*v1 = (m1+m2)*v3
v3= (m2*v2 – m1*v1) / (m1+m2)
v3 = (2kg*7m/s – 10kg*1m/s) / (10kg+2kg)
v3 = 0,33 m/s
Wózek z kulą porusza się w tym kierunku, w którym toczyła się kula.
zad 2
m1= 11000 kg
m2= 54 kg
v1 = ?
v2 = 900 m/s
Po = Pk
Po=(m1+m2)* V
V= 0 – na początku działo jest w spoczynku
0=m2*v2 – m1*v1
m1*v1 = m2*v2
v1= (m2*v2) / m1
v1= (54kg*900m/s) / 11000kg
v1 = 4,42 m/s